Parametric study of a diffuser for horizontal axis wind turbine power augmentation - Nathnael Bekele; Wondwossen Bogale (AIMS Energy, 2019)
For a wider dissemination and implementation of small wind turbines for rural electrification in developing countries, the cost of the system must be reduced. When searching for systems that are efficient and economical, Diffuser Augmented Wind turbine seems to have a potential role by increasing the power output and reducing the cost of the system most importantly at low speeds. In this paper, a detailed study has been done on Diffuser Augmented Wind Turbines to find a parametric relationship for power augmentation for horizontal axis wind turbines. A suitable diffuser was selected and its parameters were identified and their relationships were formulated based on Computational Fluid Dynamics. The result has been validated using experimental analysis. Based on the result, the power output and performance of a wind turbine is improved while using diffuser. The result shows the velocity peaks at a location immediately after the diffuser inlet. The velocity, then, levels off and further decreases as the flow continues to the diffuser outlet and exits it. This suggests a possible location of a wind turbine at the vicinity of the inlet. Based on the result, the length of the diffuser and the flange height were the major parameters to be considered. Maximum velocity ratios up to 1.5 were obtained with potential power increase of more than 2 times. It has also been observed that velocity ratios of up to 1.3 can be achieved with more compact diffusers potentially reducing the cost of the diffuser and the whole system. The mathematical relations obtained for the major parameters and the velocity ratio can be used in the performance prediction and optimization of a diffuser. Finally, possible directions for further research are recommended considering that this work shows a good agreement with previous works and predictions.